Consumers’ Perception regarding Service Quality in Aviation Sector in Agartala - Krishnankutty, Raveesh (Information Management and Business Review, 2011)
This paper intend to identify the factors affecting the consumer perception (when people chooses the services by compulsion not by choice) regarding the service quality among three domestic airlines namely Spice Jet, Indigo and Kingfisher, service providers in Agartala and to identify the most important factor in case of each domestic airlines. For achieving this objective a questionnaire was framed according to SERVPERF model and data from 110 subjects. Factor analysis and then regression analysis was carried out for extracting the factors and identifying the most important factor. We found that among the three airline service providers the number of factors loaded is different. Additionally, in case of Spice Jet and Indigo ‘assurance’ and in case of Kingfisher ‘safe and promptness’ factor is found to be most important factor.